PREVALENCE OF PARASITIC CONTAMINATION OF LEAFY GREEN VEGETABLES IN MISURATA, LIBYA - O Elmajdoub Layla; A. Omar Mosaab; S. Al-Aboudy Mohammed; F Abosheba; S Elzwawi (Российский паразитологический журнал, 2019)
This study was undertaken to determine the prevalence of parasitic contamination in leafy green (lettuce and rocket) vegetables, samples of which were taken up from different regions of Misurata, Libya. A total of 112 raw vegetable samples randomly selected from farms and markets were subsequently examined by a concentration method and then assayed by light microscopy. It was found that 56.3% of the green vegetables were contaminated with different intestinal parasites, the parasites included cysts of Giardia spp., Enatmeaba histolytic a, Entameaba coli , Coccidia spp. oocysts, Balantidium coli and eggs of Hymenolepis nana., Ascaris lumbricoides., Toxocara spp., Strongyloides spp., Trichius trichura and Trichostronylus spp. The highest rate of contamination was detected in rocket (64.3%) while contamination was lower in green lettuce (48.2%). Toxocara spp. eggs were the highest prevalent parasite detected in green vegetables (27%) with the highest score density found in the rocket. Toxocara was followed by Entameaba coli cysts (24%), Coccidia spp. Oocysts (22%), Enatmeaba histolytica cysts (19%), Giardia spp. cysts (10%), and Hymenolepis nana eggs (8%). There were lesser rates of contamination from the parasites Strongyloides spp., Trichius trichura and Trichostronylus spp. There was no significant difference between single and mixed contamination of rocket and lettuce P>0.05. However, there was a statistical difference between protozoa and helminths contamination of rocket and lettuce (P≤0.01). We conclude these findings may have important implications for global food safety and confirm that green vegetables are a point of transmission of intestinal parasites to humans and so are a threat to public health in Misurata, Libya.